Geographic distribution, ecology, and phylogenetic affinities of thyroptera lavali Pine 1993 (2004)
ABSTRACT: Thyroptera lavali (Chiroptera: Thyropteridae) is a rare Neotropical species that until now has been recorded from only five localities in the Amazonian rainforests of Peru, Ecuador, Venezuela, and Brazil. Fewer than 10 specimens of T. lavali exist and, accordingly, little is known about its distribution, natural history, and phylogenetic affinities. We report new records for the species from southeastern Peru. Together with other recently published records, these expand the known range of the species considerably, as well as increase our knowledge of its ecology. Thyroptera lavali seems to prefer primary forest near swamps, and probably roosts in palms; its reproductive pattern is similar to that of other Neotropical insectivorous bats, with parturition at the beginning of wet season. Finally, we used two different data matrices to assess its phylogenetic relationships: one of discrete morphological characters, the other of DNA sequences of mitochondrial genes. Both data sets support a sister relationship between T. lavali and T. tricolor, with T. discifera as the basal member of the genus Thyroptera.